REVISITING INTEGRATED APPROACHES TO FORENSIC INVESTIGATION AND THEIR ANTICIPATED DEVELOPMENT - N. Mylis; V. Orlova (Теория и практика судебной экспертизы, 2014)
The paper addresses relevant concerns in the use of integrated approaches to forensicinvestigation, their current status, key debating points and development prospects.